Estimating the temperature optima of soil priming. (January 2023) - Alster, Charlotte J.; van de Laar, Allycia; Arcus, Vickery L.; Numa, Kristyn B.; Wall, Aaron M.; Schipper, Louis A.
Abstract: Understanding the temperature response of soil microbial respiration is essential for predicting carbon (C) losses as the planet warms. As fresh, labile C inputs can further accelerate soil C loss (priming effect), determining if priming is temperature sensitive has important implications for global C cycling and remains relatively unexplored. We conducted a series of 5-h incubations for five different soil orders at 40 discrete temperatures with added 13 C-labelled glucose and measured soil microbial respiration. We then estimated the temperature response of microbial respiration attributable to (1) the added glucose, (2) the soil organic matter (SOM), and (3) soil priming. The relative proportion of the priming response varied with temperature and the magnitude of these changes differed by soil type. We found that the temperature response of microbial respiration attributable to priming and to the added glucose were unimodal and could be modelled using Macromolecular Rate Theory (MMRT). This suggests that biological mechanisms play a strong role in shaping the temperature response of priming. In contrast, respiration derived from SOM typically increased continuously with increasing temperature. Using MMRT we estimated a temperature optimum ( T o p t ) and inflection point ( T inf ) from each of the temperature response curves for microbial respiration derived from the added glucose and from soil priming. The temperature response of respiration from soil priming ( T o p t = 30.6 °C and T inf = 12.8 °C) was significantly lower than from the added glucose ( T o p t = 42.4 °C and T inf = 14.5 °C), which indicates that priming is more temperature sensitive. This study demonstrates that soil priming itself is temperature sensitive and responds differently to warming than the bulk soil, which may alter soil C stocks in ways not previously predicted. Further exploration of the temperature sensitivity of priming therefore warrants inclusion in future discussions of soil microbial responses to climate change. Graphical abstract: Image 1 Highlights: Temperature response of soil priming was measured for five soil orders. The temperature optima of respiration attributed to soil priming was distinct. Temperature response of soil priming can be modelled by Macromolecular Rate Theory. The relative proportion of priming varied with temperature and soil type.